2021
DOI: 10.3389/fcell.2021.709069
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA Double Homeobox A Pseudogene 8: A Novel Oncogenic Propellant in Human Cancer

Abstract: A growing number of studies are reporting important roles played by long non-coding RNAs (lncRNAs) in various pathological and physiological processes. LncRNAs are implicated in numerous genomic regulatory functions at different levels, including regulation of transcription, post-transcriptional processes, genomic stability, and epigenetic genome modifications. Double homeobox A pseudogene 8 (DUXAP8), a novel lncRNA, has been reported to be involved in many cancers, including gastric, colorectal, esophageal, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(102 reference statements)
1
3
0
Order By: Relevance
“…DUXAP8 is a biomarker and therapeutic target of various cancers that is upregulated in GC, promotes cell proliferation and migration, and then accelerates the development of GC 32 , and this study verified the upregulation of DUXAP8 in GC. Previous studies have shown that lncRNA TP53TG1 can not only inhibit the development of GC by regulating the stability of CIP2A34 30 , but also play a promoting role in cancer development.…”
Section: Discussionsupporting
confidence: 69%
“…DUXAP8 is a biomarker and therapeutic target of various cancers that is upregulated in GC, promotes cell proliferation and migration, and then accelerates the development of GC 32 , and this study verified the upregulation of DUXAP8 in GC. Previous studies have shown that lncRNA TP53TG1 can not only inhibit the development of GC by regulating the stability of CIP2A34 30 , but also play a promoting role in cancer development.…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies have found that silencing DUXAP8 expression can inhibit cell proliferation and promote apoptosis by targeting miR-26b-5P (32). DUXAP8 is involved in the initiation of many tumors and has the potential as a therapeutic target (33). LncRNA PWAR6 regulates proliferation and migration by epigenetically silencing YAP1 in tumorigenesis of pancreatic ductal adenocarcinoma (34).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoid-specific helicase can inhibit ferroptosis in lung cancer cells, and LSH knockout decreases SLC2A3 and induces ferroptosis, which implies that SLC2A3 may be involved in inhibiting ferroptosis ( Jiang et al, 2017 ). Double homeobox A pseudogene 8 (DUXAP8), as a novel, long noncoding RNA, is associated with a number of cancers, including liver, colorectal, bladder, oral, ovarian, lung, and pancreatic tumors ( Xue et al, 2021 ). However, it is rarely studied in ferroptosis and, whether the DUXAP8-hsa-miR-378e/378f-SLC2A3 ceRNA network we constructed is involved in the regulation of ferroptosis, remains to be verified.…”
Section: Discussionmentioning
confidence: 99%